A Comprehensive Review of Pests, Pesticides and Residue Detection Techniques in Mushroom - Tulasi B; Bhuvaneswari K; Sake Manideep; Sai Kumar; Selvi C; Ch Nagarani; Thrilekha D (Archives of Current Research International, 2024)
Mushrooms are valued for their dietary benefits and medicinal properties, being rich in proteins, minerals, vitamins, fiber, and essential amino acids. They offer significant health benefits, including the prevention of hypercholesterolemia and cardiovascular diseases, and possess antitumor, antiviral, antihypertensive, anti-inflammatory, and immunomodulating properties. Global mushroom production has seen substantial growth, particularly in Asia. However, mushroom cultivation is challenged by various insect pests, leading to significant crop losses. Pesticides are frequently applied to control pests in mushroom cultivation, but their use can lead to the presence of pesticide residues in the mushrooms, raising concerns about food safety. To detect these low levels of residues, multiresidue analytical methods are crucial. Among these, the QuEChERS method stands out as the most commonly used due to its sensitivity, selectivity, and accuracy in determining multiple pesticide residues simultaneously. These methods are capable of identifying various pesticide compounds in a single analysis, effectively addressing the specific biological characteristics of mushrooms. The maximum residue levels (MRLs) for pesticide residues in mushrooms differ, with strict guidelines enforced by regulatory authorities. This paper provides a comprehensive review of the pests that affect mushroom cultivation, the pesticides utilized, and the analytical techniques developed for the detection of pesticide residues in mushrooms.